STRATEGI INOVASI SERVICES DIGITAL KORLANTAS POLRI UNTUK PENINGKATAN KINERJA ORGANISASI - Tri Julianto Djatiutomo; Zulkifli, Zulkifli; Mombang Sihite (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to Strategy the digital service innovation strategy at the Korlantas Polri institution.. This research uses qualitative research methods. Qualitative analysis using SWOT, IFE & EFE and QSPM. The results of strategy analysis research through the input strategy stage with IFE, EFE, &CPM matching stage with TOWS and decision stage with QSPM, the strategy used from the QSPM results are alternative strategy of Development of HR Competency Korlantas Polri into Digital HR. Implication: The Korlantas Polri must carry out organizational transformation according to the vuca era with adaptive and agile concepts and adapt to the police's precision